Hello
assuming the triangle is the figure below
the sum total of all angles in a triangle is equal to 180 degree
![\begin{gathered} (4x-9)+(6x-9)+(x-9)=180\text{ } \\ \text{sum total of angles in a triangle is equal to 180 degree} \\ 4x-9+6x-9+x-9=180 \\ \text{collect like terms} \\ 11x-27=180 \\ 11x=180+27 \\ 11x=207 \\ x=(207)/(11) \\ x=18.82^0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mr7vrvhqp2jobltz8pxoslnpo8x62jakcy.png)
to find the degree measure in each angle, we can substitute x into the expression
![\begin{gathered} 4x-9 \\ x=18.82^0 \\ 4(18.82)-9=66.28^0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y1q8un350rl13twbipr7mb5suf4q8rtrvo.png)
![\begin{gathered} x-9 \\ \text{substitute x into the expression} \\ x=18.82^0 \\ 18.82-9=9.82^0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jht90bmiuh3zheopqpj6n89ju9064tiy9c.png)
![\begin{gathered} 6x-9 \\ x=18.82 \\ \text{substitute x into the expression} \\ 6(18.82)-9=103.92^0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4wieuv7giu884uuuyykl4ad8q97j2lkxna.png)
the degree measure of the angles are 66.28, 9.82 and 103.92 degrees respectively.
to prove the solution, the sum of the angles must be equal to 180 degree
![66.28^0+9.82^0+103.92^0=180^0](https://img.qammunity.org/2023/formulas/mathematics/college/lb4u2cunjqxw5opvq9dg5rreex6sbsog19.png)